Framework Employee Empowerment Impact on the Relationship Between Employee Innovation and Organizational Performance at Abu Dhabi National Oil Company (ADNOC) - admin, admin; Hassani, Ali Hassan Hassan Al; Sarpin, Norliana (Tropical Scientific Journal, 2025)
Objective: This study aims to examine the relationship between innovation constructs, specifically Product Innovation and Process Innovation, and organizational performance in the oil and gas sector, with a particular focus on the mediating role of employee empowerment within the Abu Dhabi National Oil Company (ADNOC). Research Method: A quantitative research approach was employed, collecting data from 302 ADNOC employees. The study utilized the Structural Equation Modelling technique using Partial Least Squares (SEM-PLS) in the SmartPLS software to develop and validate the proposed research framework Findings: The results revealed significant indirect effects of both product and process innovation on organizational performance through the mediating role of employee empowerment. The findings demonstrate that employee empowerment partially mediates these relationships, underscoring its strategic importance in maximizing the impact of innovation on performance outcomes. Originality: This study contributes to the limited empirical research in the oil and gas industry by highlighting employee empowerment as a crucial mechanism linking innovation efforts to improved organizational performance. The framework offers practical implications for leveraging human capital in innovation strategies within high-risk and complex industrial environments